Flame retardant properties of phosphorylated derivatives of malonic ester - Sal’keeva, L.K.; Taishibekova, E.K.; Minaeva, E.V.; Shibaeva, A.K.; Kasenov, R.Z.; Sal’keeva, A.K.; Muratbekova, A.A. (Springer, 2013)
Thermal stability of the phosphorylated derivatives of malonic ester synthesized by the Michaelis-Becker reaction was studied. The flame-retardant efficiency of the phosphonomalonic ester was assessed by the flame-tube technique measuring the weight loss of wood samples impregnated with the studied compound.